Unveiling the impact of imidazole derivative with mechanistic insights into neutralize interfacial polymerized membranes for improved solute-solute selectivity. (15th February 2023) - Istirokhatun, Titik; Lin, Yuqing; Kinooka, Ken; Shen, Qin; Zhang, Pengfei; Jia, Yuandong; Matsuoka, Atsushi; Kumagai, Kazuo; Yoshioka, Tomohisa; Matsuyama, Hideto
Highlights: Membrane surface modification with imidazole derivative compounds were achieved. Imidazole derivatives were grafted onto PA membrane via surface amination with TMC. Electrostatic repulsion was neutralized while size sieving obstruction was strengthened. Solute-solute separation toward nutrient recovery and micropollutant removal was achieved. High water permeance and excellent antifouling/anti-biofouling properties were obtained. Abstract: Domestic wastewater (DWW) contains a reservoir of nutrients, such as nitrogen, potassium, and phosphorus; however, emerging micropollutants (EMPs) hinder its applications in resource recovery. In this study, a novel class of nanofiltration (NF) membranes was developed; it enabled the efficient removal of harmful EMP constituents while preserving valuable nutrients in the permeate. Neutral (IM-N) and positively charged (IM-P) imidazole derivative compounds have been used to chemically functionalize pristine polyamide (PA) membranes to synchronously inhibit the hydrolysis of residual acyl chloride and promote their amination. Owing to their distinct properties, these IM modifiers can custom-build the membrane physicochemical properties and structures to benefit the NF process in DWW treatment. The electroneutral NF membrane exhibited ultrahigh solute-solute selectivity by minimizing the Donnan effects on ion penetration (K, N, and P ions rejection < 25%) while imposing remarkable size-sieving obstruction against EMPs (rejection ratio > 91%). Moreover, the hydrophilic IM-modifier synergistically led to enhanced water permeance of 9.2 L m −2 h −1 bar −1, reaching a 2-fold higher magnitude than that of the pristine PA membrane, along with excellent antifouling/antibacterial fouling properties. This study may provide a paradigm shift in membrane technology to convert wastewater streams into valuable water and nutrient resources. Graphical abstract: Image, graphical abstract